KARAKTERISTIK MENOPAUSE PADA PERAWAT DI RSUP SANGLAH DENPASAR TAHUN 2021 - Kirana, Ni Wayan Kartika Candra; Surya, I Gede Ngurah Harry Wijaya; Manuaba, Ida Bagus Gede Fajar; Mulyana, Ryan Saktika (Universitas Udayana, 2022)
The age of menopause varies in each woman, due to differences in the characteristics of certain factors that are thought to have an effect. This study aims to determine the age of menopause and the characteristics of education level, marital status, parity, age of menarche, age of first birth, history of hormonal contraceptive use, and Body Mass Index in postmenopausal nurses at Sanglah General Hospital Denpasar in 2021. This study is an observational descriptive study with a cross-sectional approach. The sample consisted of 60 respondents who were collected by total sampling method. Data were collected through interviews using a questionnaire. The results showed that 88,3% experienced menopause at the age of >45 years with the most distribution at the age of 50 years (30%). The characteristics of respondents were as follows, namely 100% in married, 88,3% completed D3/S1/S2/S3, 73,3% had given birth to 1-2 children, 88,3% gave birth to their first child at the age of 20-29 years, 58,3% menarche at age > 14 years, 61,7% never used hormonal contraception, 51,7% are obese I. The results of this study are expected to be used as a basis for further research to determine the association between the characteristics of a woman and menopausal age. Keywords : menopause, menopausal age, characteristics.